2002
DOI: 10.1097/00024382-200211000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Immediate S-100B and Neuron-Specific Enolase Plasma Measurements for Rapid Evaluation of Primary Brain Damage in Alcohol-Intoxicated, Minor Head-Injured Patients

Abstract: The neuroproteins S-100B and neuron-specific enolase (NSE) released into the circulation are suggested to be reliable markers for primary brain damage. However, safe identification of relevant post-traumatic complications after minor head injury (MHI) is often hampered by acute intoxication of the patients. The objective of this study was to determine the diagnostic validity of immediate plasma measurements of S-100B and NSE in comparison with neurological examinations and cerebral computed tomography (CCT) fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 30 publications
3
65
1
3
Order By: Relevance
“…4,12,17 In contrast, our results showed no significant correlation among alcohol, S100B, and NSE levels. Patient age was not a significant risk factor in our study.…”
contrasting
confidence: 96%
See 1 more Smart Citation
“…4,12,17 In contrast, our results showed no significant correlation among alcohol, S100B, and NSE levels. Patient age was not a significant risk factor in our study.…”
contrasting
confidence: 96%
“…5,17,18,24 On the other hand, some studies question the prognostic value in clinical routine: A study conducted in professional soccer players showed a confounding effect of high-intensity exercise on S100B levels in serum. 28 Another study featuring 44 patients with severe head injury found no significant correlation between contusion volume and NSE levels.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma S100␤ Protein Assay-S100␤ is a protein in brain and, when found in the plasma, is a marker of brain damage (17,18). Sandwich enzyme-linked immunosorbent assay was performed for measurement of the level of S100␤ protein in 20 l of plasma using rabbit polyclonal anti-S100␤ protein antibodies (Santa Cruz Biotechnology).…”
Section: Methodsmentioning
confidence: 99%
“…Choline Deprivation-The brain protein S100␤, when found in the plasma, is a marker of brain damage (17,18). S100␤ was not detected in the plasma of CS-and CD-Pemt Ϫ/Ϫ mice or in CS-and CD-Mdr2…”
Section: Brain Damage Was Not Detected Duringmentioning
confidence: 99%
“…The serum levels of S100B increases rapidly after a traumatic brain injury and some studies have reported a 10-15 fold increase above baseline levels, followed by a significant decrease the next 4-6 hours due to its short half-life (10,27,28,38,48,63). An increased level of S100B after minor head traumas has been reported to be associated with pathological findings on CT scans (9,36), prolonged in-hospital stays (38), prolonged absence from work (59), post concussive complaints (14,50) and disability one year after the incident (53). In addition, S100B is associated with the Glasgow Coma Scale score at admission and the outcome after more severe head injury (46,64).…”
Section: Introductionmentioning
confidence: 99%